Evaluating teen driving knowledge and behaviors following educational outreach - Kathy Monroe; Michele Nichols; Marie Crew; Leslie Brown; William King (BMC, 2020)
Abstract Background Teen driving educational events are an effective strategy to increase adolescent drivers' awareness of safe driving practices. The objectives of this study were to evaluate changing rates of self-reported driving practices and knowledge of the state Graduated Driver Licensing laws (GDL) by teens over a nine-year period in a single state. Methods This was a prospective observational study of high school students ages 14 to 19 years old. Paper surveys were sent to the high schools participating in teen driving educational events (9 schools in 2009 and 4 schools in 2018). Students in those schools completed surveys prior to the events. Students completing the anonymous survey were invited to the event. Questions evaluated awareness of state GDL and safe and risky driving behaviors. Statistical comparisons of survey answers from 2009 to 2018 were analyzed using the z test of proportions (2 tailed, alpha 0.05). Results A total of 397 students participated in 2018 with ages ranging from 14 to 19 years. Racial distribution was 81% white, 14% black, and there were 57% female participants. Only 69% (n = 273) reported "always" wearing their seatbelt. When asked about high risk behaviors, 78% (n = 309) of adolescents reported they personally "never" text while driving; 97% (385); never drive after drinking, and 87% (n = 344) never ride with someone who has been drinking. Compared to 2009 participants (1304 students, 9 schools from central part of state), the students in 2018 (4 schools scattered across state) reported wearing seatbelts "always" (n = 69% vs 39%; p < 0.001); "never texting while driving" (78% vs 33%; p < 0.001); and "never drinking and driving" (97% vs 88%; p < 0.001). No significant difference in rates of students having taken a driving education class nor driving over speed limit were reported. Conclusion Results are encouraging that participants in 2018 report more use of seatbelts, less texting while driving, less drinking while driving and lower numbers of being in MVC than in 2009. However, rates of high-risk driving behaviors are still concerning.